What will happen to the internationalization of higher education and student mobility after COVID-19? - Gómez López, Pamela (2020)
Internationalization is a process that is carried out in higher education institutions with different objectives and with its implementation it seeks to integrate an international and intercultural perspective in the functions of universities; This process is made up of various strategies, and among the best known is student mobility. In recent decades, internationalization has become more relevant, however, it is a process that still lacks a comprehensive understanding and is carried out in accordance with the intentions and resources of the institutions. With the arrival of the COVID-19 disease, internationalization and student mobility are facing an uncertain future, faced with the urgency of solving other needs in institutions, which is why other ways of implementing it are being explored.